Development of surface modifications on titanium for biomedical applications - Maia Sabino, Roberta, author; Popat, Ketul C., advisor; Martins, Alessandro F, advisor; Herrera-Alonso, Margarita, committee member; Li, Yan Vivian, committee member; Wang, Zhijie, committee member (Colorado State University. Libraries, 2021)
For decades, titanium-based implants have been largely employed for different medical applications due to their excellent mechanical properties, corrosion resistance, and remarkable biocompatibility with many body tissues. However, even titanium-based materials can cause adverse effects which ultimately lead to implant failure and a need for revision surgeries. The major causes for implant failure are thrombus formation, bacterial infection, and poor osseointegration. Therefore, it is essential to develop multifunctional surfaces that can prevent clot formation and microbial infections, as well as better integrate into the body tissue. To address these challenges, two different surface modifications on titanium were investigated in this dissertation. The first one was the fabrication of superhemophobic titania nanotube (NT) surfaces. The second approach was the development of tanfloc-based polyelectrolyte multilayers (PEMs) on NT. The hemocompatibility and the ability of these surfaces to promote cell growth and to prevent bacterial infection were investigated. The results indicate that both surface modifications on titanium enhance blood compatibility, and that tanfloc-based PEMs on NT improve cell proliferation and differentiation, and antibacterial properties, thus being a promising approach for designing biomedical devices.
Keywords: superhemophobic surfaces; titania nanotubes; layer-by-layer; titanium surfaces; tanfloc